Helen Leach, Mary Browne, Raeline Inglis: The Twelve Cakes of Christmas: an evolutionary history with recipes - Geggus, Pam (Petits Propos Culinaires, 2012)
Helen Leach, Mary Browne, Raeline Inglis: The Twelve Cakes of Christmas: an evolutionary history with recipes: Otago University Press, 2012, 192 pp., hardback: £24.50.